Implementation of The Tandur Learning Model in Increasing Student Social Knowledge Learning Outcomes Class V at SDN 123 Inpres Ujung Lau, Takalar Regency - Syamsunardi Syamsunardi; Nur Syam (ARRUS Journal of Social Sciences and Humanities, 2023)
The application of the TANDUR learning model in improving learning outcomes in social science subjects in social science in Class V students at SDN 123 Ujung Lau, Takalar Regency. This study aims to determine the effect of applying the TANDUR learning model to the learning outcomes of social science subjects for Class V students at SDN 123 Ujung Lau, Takalar Regency. the research used is classroom action research. The subjects in this study were all fifth grade students at SDN 123 Ujung Lau, Takalar Regency, with a total of 19 students, 7 male students and 12 female students. The data collection techniques used were observation, tests, and documentation, while the data analysis used was descriptive qualitative data analysis. Research on the TANDUR learning model on learning outcomes in natural science subjects in Class V Students at SDN 123 Ujung Lau, Takalar Regency is said to increase where there is an increase in student learning outcomes in social science learning seen from the value of student learning outcomes with a score of 1250 or 66% in the cycle 1 then increased to 1560 or 82% in cycle 2. Because it had reached the completeness criteria, namely 80% of students scored more than or equal to the minimum completeness criteria (70), this study was said to be successful. From the increase in student learning outcomes it is known that there is an effect of applying the Tandur Learning model on learning outcomes in social science subjects for Class V SDN 123 Ujung Lau, Takalar Regency.